PENGUJIAN LOSS AVERSION INVESTOR DI BURSA EFEK INDONESIA (STUDI PADA PERUSAHAAN INDEKS KOMPAS100 YANG TERCATAT DI BURSA EFEK INDONESIA) - Zaida Fatima; Syarifah Rahmawati (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2021)
This study aims to examine the existence of loss aversion behavior bias or in practice it is called the disposition effect on Kompas100 Index companies listed on the Indonesian Stock Exchange. Testing of one of these bias of investor behavior was carried out for five years, from 2015 – 2019 period. This study uses data on holding period, illiquidity, and stock returns, as well as firm size proxied by market capitalization as a control variable. The behavioral bias that causes the disposition effect is indicated when illiquidity has a positive and significant effect on the holding period. Meanwhile, regret avoiding disposition effect is indicated if return has a negative and significant effect on the holding period. To see this effect, an analysis was carried out using multiple linear regression tests. The results showed that there was a disposition effect and regret avoiding disposition effect on Kompas100 Index companies listed on the Indonesia Stock Exchange.